Benchmarking Real-time Operating Systems for use in Radio Base Station applications - Örnvall, Oskar (My University, 2012)
The support systems for Radio Base Stations (RBS) are getting increasingly advanced. There are demands to support numerous RBS configurations, multiple and alternative energy sources such as wind a solar, different cooling systems and alarm handling. The support system is desired to be modular, reusable and upgradable. This requires more advanced software solutions utilizing the facilities of a real-time operating system. Real-time capabilities and performance are important factors when selecting a real-time operating system for an application. There is no standard method or tool for benchmarking real-time operating systems, neither is there an independent organization that verify and publish benchmark results of real-time operating systems. This thesis studies benchmarking of real-time operating systems which could be suitable for Radio Base Station support systems. A survey of small real-time operating system was done that focus on kernel services and available middleware. Different benchmarking methods were studied and presented in a benchmarking survey. A portable benchmark tool based on rhealstone was implemented and is discussed in terms of portability and the information it provides. Two real-time operating systems Quadros RTXC and Freescale MQX was benchmarked. The results show there can be a considerable difference in performance of small real-time operating systems. The thesis ends with a discussion about benchmarking of real-time operating systems in general that emphasises the importance of requirements and that the selection of scheduling algorithm, priority assignments and the design of the application plays a major role in obtaining the best performance. Extending the benchmark tool to include stress testing, network performance, memory footprint and power consumption is suggested. Finally it is called for an independent organization which could verify benchmark results of real-time operating systems and provide benchmarking tools.
Keywords: Datavetenskap (datalogi); Informations- och kommunikationsteknik; Computer Science; Information & Communication Technology